Clinical classification of adult patients with chronic intestinal failure due to benign disease: An international multicenter cross-sectional survey. Issue 2 (April 2018) - Pironi, Loris; Konrad, Denise; Brandt, Chrisoffer; Joly, Francisca; Wanten, Geert; Agostini, Federica; Chambrier, Cecile; Aimasso, Umberto; Zeraschi, Sarah; Kelly, Darlene; Szczepanek, Kinga; Jukes, Amelia; et al.
Summary: Background & aims: The aim of the study was to evaluate the applicability of the ESPEN 16-category clinical classification of chronic intestinal failure, based on patients' intravenous supplementation (IVS) requirements for energy and fluids, and to evaluate factors associated with those requirements. Methods: ESPEN members were invited to participate through ESPEN Council representatives. Participating centers enrolled adult patients requiring home parenteral nutrition for chronic intestinal failure on March 1st 2015. The following patient data were recorded though a structured database: sex, age, body weight and height, intestinal failure mechanism, underlying disease, IVS volume and energy need. Results: Sixty-five centers from 22 countries enrolled 2919 patients with benign disease. One half of the patients were distributed in 3 categories of the ESPEN clinical classification. 9% of patients required only fluid and electrolyte supplementation. IVS requirement varied considerably according to the pathophysiological mechanism of intestinal failure. Notably, IVS volume requirement represented loss of intestinal function better than IVS energy requirement. A simplified 8 category classification of chronic intestinal failure was devised, based on two types of IVS (either fluid and electrolyte alone or parenteral nutrition admixture containing energy) and four categories of volume. Conclusions: Patients' IVS requirements varied widely, supporting the need for a tool to homogenize patient categorization. This study has devised a novel, simplified eight category IVS classification for chronic intestinal failure that will prove useful in both the clinical and research setting when applied together with the underlying pathophysiological mechanism of the patient's intestinal failure.